Ruminal and intestinal degradation of cell wall constituents of barley, barley fibre and wheat mill run measured by the nylon bag technique - Aronen, I.; Vanhatalo, A.; Varvikko, T. (Elsevier, 1991)
Four ruminally and duodenally cannualated heifers were used to study the ruminal degradation of cell wall constituents of barley (B), barley fibre (BF) and wheat mill rum (WMR) using the nylon bag technique. The subsequent postruminal degradation of the feeds and their rumen - undegraded residues was determined by using a modified nylon bag technique, also called mobile bag technique in order to quantify the degradability of cell wall constituents in different parts of the gastro-intestinal tract.